Denmark’s Electronic Research Library: A single Virtual Research Library for Denmark - Öhrström, Bo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The Danish Electronic Research Library (DEF in Danish) is the realisation of a vision of a single virtual research library focused on the need for easy access to scientific information for researchers and students in Denmark. DEF is a large government funded project, which over a 5 year period spends 200 million Danish Kroner (27 million Euro) in order to build a national virtual research library in Denmark. The project aims to help the transition from purely paper-based services to electronic services in the library sector and focuses on organisational changes as well. This paper will describe the background and the present status of the project. The project is heavily based on co-operation on national and international level, and the strategy behind this is put forward.